Die geometry influence on the texture and microstructure development during extrusion of AZ31 and ZK60 magnesium alloy chips - Leo Hendriok; Maria Nienaber; Gerrit Kurz; Noomane Ben Khalifa (Materials & Design)
Solid state recycling by direct extrusion of metal chips can significantly reduce energy requirements in comparison to traditional recycling strategies and primary production. The process consists of cold-compacting the chips into chip-based billets and subsequent hot extrusion to the desired profile. Thereby, mechanical properties comparable to conventional profiles made from as-cast billets can be achieved. This study examines the development of microstructure and texture and their impact on the mechanical properties. Consequently, extrusion experiments are conducted using two sets of dies, namely a flat face (FF) die and an ECAP die, with magnesium alloys AZ31 and ZK60. The texture of the profiles and extrusion remainders of both dies is measured using EBSD and XRD in order to analyse the influence of the chips and deformation path on the texture development. The microstructure of the extruded chip-based profiles exhibits notable grain refinement, which can be attributed to the substantial mechanical strain introduced during milling and compaction of the chips. Furthermore, it is demonstrated that the combination of chip-based billets and FF die extrusion results in a favourable weakening of basal texture and development of a RE-like < 2–1-11 > texture component, thus causing a tilt of basal planes out of extrusion direction. Conversely, ECAP extrusion leads to an increased intensity of basal texture, highlighting the influence of deformation path on texture development. Finally, it is shown that a combination of microstructure and texture effects can result in preferable mechanical properties of chip-based profiles.